Analysis of the Effect of Population on the Amount of Waste in Jakarta - Nurrobi, Muhammad Anugerah (Universitas PGRI Sumatera Barat, 2022)
The waste problem in DKI Jakarta is getting worse. According to data from the DKI Jakarta Central Statistics Agency, the amount of waste increased from 2017 to 2021. The capacity of the Final Disposal Site (TPA) has exceeded the limit. Every day community activities grow and develop, but the waste problem cannot be controlled. With these problems, the authors make a hypothesis and correlate whether there is a relationship between the population and the amount of waste, and analyze the waste management facilities provided by the government with a significance level (⍺) of 0.05.